Prurigo Nodularis: Literature Review - Alrabiah, Khaled (International Journal of Innovative Research in Medical Science, 2023)
Multiple, hard, flesh-to-pink papules, plaques, and nodules, often seen on the extensor surfaces of the limbs, are characteristic of prurigo nodularis, a persistent skin condition. The itchy lesions may strike people of any age. It often occurs in tandem with another condition that causes constant itching, such atopic dermatitis or another dermatosis. The clinical symptoms are the primary indicators. However, there may be numerous instances when lichen simplex chronic us and hypertrophic lichen planus are indistinguishable from a clinical standpoint. Therefore, it is crucial to confirm the diagnosis by dermoscopy and histology. Many other therapy strategies are being used, including those using powerful antipruritics, immunomodulators, and neuromodulators. After a diagnosis has been made, treatment might take a long time, thus patient education and counseling are crucial to ensuring they stick with the plan. A subset of chronic prurigo, prurigo nodularis (PN) manifests as hyperkeratotic, very itchy papules and nodules that are often seen in a symmetrical pattern. PN develops with persistent pruritus in the setting of a wide variety of dermatological, systemic, neurological, or mental disorders. Although the specific pathophysiology of PN is not well understood, chronic scratching may be a primary cause. Topical steroids, capsaicin, calcineurin inhibitors, ultraviolet (UV) treatment, systemic injection of gabapentinoids, -opioid receptor antagonists, antidepressants, and immunosuppressants are the current gold standard in treating PN. Clinical trials are being conducted on cutting-edge therapeutic modalities such blockers of neurokinin-1, opioid, and interleukin-31 receptors.